Study on Elastic Response of Double-Rotor VAWTs - Saika Iwamatsu; Hideyuki Suzuki; Yasunori Nihei (Journal of Marine Science and Engineering, 2022)
This study investigates the elastic response characteristics of a floating wind turbine (FOWT) with two vertical-axis wind turbines (VAWTs), called double-rotor VAWTs. The model consists of two VAWTs mounted on a single semi-submersible floating structure and employs a single point mooring, which allows the FOWT to always self-align with the wind. Usually, a coupled analysis of the wind turbine and floating structure is used in the design of FOWTs; however, there is no coupled analysis available for VAWTs. In this study, we attempted to combine the wind turbine design software “QBlade” and the coupled wind turbine/floating body analysis code “UTWind” as one of the methods of coupled analysis of a VAWT and a floating body. Numerical simulation results were compared with experimental results using an elastic model scaled down to 1/100 of its actual model to determine the motion response and cross-sectional bending moments. The experimental results showed that the thrust of the VAWT had a particular influence on the cross-sectional forces and motion response between the two VAWTs. For cross-sectional forces, all results showed similar trends. Overall, the results of UTWind for double-rotor VAWTs are reasonable. It was also found that the pitch motion must be accurately reproduced to improve the accuracy.